School health and education: An interdisciplinary connection - Olga N. Makhubela-Nkondo (AOSIS, 2013)
For South Africa, the continent and the world as a whole, formal health literacy begins at school. Higher Education in South Africa is challenged to take heed of the World Health Organization's (WHO) (1996) definition of school health. For the WHO, school health is not merely hygiene, health promotion, health literacy or health education but a 'combination of services ensuring the physical, mental and social well-being of learners so as to maximize their learning capabilities'. The WHO Expert Committee on School Health asserts that school health can advance public health, education, social and economic development, and that the global expansion of school health attests to the value placed internationally on such programmes (WHO 1996).